Faktor Faktor Yang Berhubungan Dengan Kepuasan Peserta Pelatihan Perawat K3 Di Yayasan Appoki: Indonesian OHN Training - Satiman Satiman; Suhat Suhat; Budiman Budiman; Arif Susanto; Novie E Mauliku; Devanda Faiqh Albyn (Medical : Jurnal Kesehatan dan Kedokteran, 2026)
Background: Training is a crucial investment in human resource development. Participant satisfaction serves as an indicator of training success and influences motivation to apply training outcomes.Objective: This study aimed to analyze factors influencing training participant satisfaction, including material quality, facilitator competence, training methods, training benefits, and behavioral changes at APPOKI Foundation.Methods: This cross-sectional study employed accidental sampling from available training participants (n=33 respondents; response rate 66%). A structured questionnaire using a 4-point Likert scale (1=Very Dissatisfied to 4=Very Satisfied) measured four main variables, demonstrating validity and reliability (Cronbach's Alpha 0.886–0.974). Analysis included univariate (frequency, mean), bivariate (Chi-Square nonparametric), multivariate (multiple logistic regression), and pre-post test comparison (Wilcoxon nonparametric). Results: Majority were female (69,7%), bachelor's degree holders (66,7%), and had <5 years work experience (51,5%). Satisfaction rate was 33,3% with quality assessments on materials (42,4%), facilitator (39,4%), methods (33,3%), benefits (36,4%), and behavioral changes (36.4%). Wilcoxon test showed significant post-test increase (mean 79,39 to 89,70; p=0,002). Bivariate analysis showed five variables significantly related to satisfaction: material quality (p=0,001; PR=3.3), facilitator competence (p=0,001; PR=4.1), training methods (p=0,001; PR=10,5), and benefits (p=0,001; PR=3,6). Multivariate analysis showed training material quality as the only dominant factor significantly influencing satisfaction. Participants rating materials as quality had 71,4% probability of satisfaction. Conclusion: Occupational Health and Safety Nurse training effectively improved learning outcomes. Training material quality is the dominant factor determining satisfaction, with participants rating materials as quality showing high satisfaction (71,4%). Focused improvements on material quality are needed through comprehensive needs assessment, content alignment with participant needs, practical case studies, and regular material updates.